EXPLORING TRENDS AND FOCUS OF SCIENCE LITERACY RESEARCH: BIBLIOMETRIC ANALYSIS 2019-2024 - Anisa O. S Pratama (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to analyze trends and research focuses on science literacy using a bibliometric approach. The research employs bibliometric tools such as VOSviewer and databases like Scopus to map and analyze research trends from 2019 to 2024. Keywords used in this study include